Kebutuhan Bahan Ajar Bermuatan Kearifan Lokal: Analisis dalam Pembelajaran Keterampilan Membaca Bahasa Arab dalam Konteks Pendidikan Tinggi - Fitra, Muh. Naufal; Machmudah, Umi; Penny Respati (Shaut al Arabiyyah, 2025)
This study aims to identify the need for teaching materials loaded with local wisdom in learning Arabic reading skills in universities, with a focus on the Arabic Language Education Department at IAIN Bone. This study uses a qualitative descriptive approach, with data collected through analysis of student profiles and characteristics, student reading preferences, observation of teaching materials used, analysis of the vision and mission of the institution, and interviews with Arabic lecturers. The results of the study show that the teaching materials used today do not fully reflect local cultural values, even though they are in accordance with students' reading preferences. Bugis folklore and legends, such as Sijello To Mampu, Putri Tadampali, and La Mellong, have great potential to be integrated into teaching materials because they contain moral messages and character values that are relevant to educational needs. In addition, the vision and mission of IAIN Bone which emphasizes local wisdom supports the importance of developing contextual and culture-based teaching materials. This study emphasizes the need to develop teaching materials that are not only interesting and relevant academically but also loaded with local wisdom to support cultural preservation and the formation of student identity. The recommendations given include the preparation of learning modules based on Bugis folklore and the use of technology to document and disseminate teaching materials.